Errors in Recorded Security Prices and the Turn-of-the-Year Effect - Thomson, James B. (Journal of Financial and Quantitative Analysis, 1989)
comments and suggestions. Working papers of the Federal Reserve Bank of Cleveland are preliminary materials circulated to stimulate discussion and critical comment. The views stated herein are the author's and not necessarily those of the Federal Reserve Bank of Cleveland or of the Board of Governors of the